Uncommon Metastatic Spread of Endometrial Carcinoma to the Posterior Thoracic Wall and Genital Tract in a Young Adult: A Case Report - Phindo Mawardinata; Dodi Suardi; Ali Budi Harsono; Christian Homenta; Ferry Iskandar Kharisma Sinaga; Sulaeman Andrianto Susilo; Bethy S. Hernowo; Reza Rinaldy Harahap; Munawar Adhar Lubis (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Endometrial carcinoma is a common gynecologic malignancy that predominantly affects postmenopausal women. Approximately 15% of cases occur in premenopausal patients, and more than 1% are diagnosed in women younger than 40 years. Distant metastases are uncommon and typically involve lymph nodes, lungs, or liver, whereas cutaneous and genital metastases are exceptionally rare. The micropapillary growth pattern, initially described in breast carcinoma, has also been identified in various organs and is associated with aggressive biological behavior, including frequent lymphovascular invasion and widespread dissemination. Case Report: A case of a 24-year-old woman with a prior history of micropapillary carcinoma excised from the posterior thoracic wall is reported. The patient presented with palpable vulvar and cervical masses. Pelvic MRI and PET-CT revealed stage IV C endometrial carcinoma with extensive dissemination involving the cervix, vulva, vagina, peritoneum, thoracic wall, and pleural cavity. Histopathological and immunohistochemical analyses confirmed endometrioid carcinoma with micropapillary features. Conclusion: This study demonstrates that the rare presentation of micropapillary endometrial carcinoma in a young patient highlights the importance of comprehensive diagnostic evaluation when unusual metastatic sites are encountered, to guide treatment and multidisciplinary management. Abstrak Pendahuluan: Karsinoma endometrium merupakan keganasan ginekologi yang umum dan terutama mengenai wanita pascamenopause. Sekitar 15% kasus terjadi pada pasien pramenopause dan lebih dari 1% pada wanita berusia di bawah 40 tahun. Metastasis jauh jarang terjadi dan biasanya melibatkan kelenjar getah bening, paru, atau hati, sedangkan metastasis ke kulit dan traktus genital sangat jarang dilaporkan. Pola pertumbuhan mikropapiler, yang awalnya dideskripsikan pada karsinoma payudara, juga ditemukan pada berbagai organ dan dikaitkan dengan perilaku biologis agresif, termasuk invasi limfovaskular dan penyebaran luas. Laporan Kasus: Dilaporkan kasus wanita berusia 24 tahun dengan riwayat karsinoma mikropapiler yang sebelumnya dieksisi dari dinding toraks posterior, datang dengan massa vulva dan serviks yang teraba. MRI pelvis dan PET-CT menunjukkan karsinoma endometrium stadium IV C dengan penyebaran luas ke serviks, vulva, vagina, peritoneum, dinding toraks, dan rongga pleura. Pemeriksaan histopatologi dan imunohistokimia menegakkan diagnosis karsinoma endometrioid dengan gambaran mikropapiler.Kesimpulan: Penelitian ini menunjukkan bahwa presentasi langka karsinoma endometrium dengan pola mikropapiler pada pasien usia muda menekankan pentingnya evaluasi diagnostik komprehensif pada lokasi metastasis tidak lazim untuk menentukan terapi dan tata laksana multidisiplin.